Anisotropies of ultrahigh energy cosmic rays diffusing from extragalactic sources - Harari, Diego Dario (2014)
We obtain the dipolar anisotropies in the arrival directions of ultrahigh energy cosmic rays diffusing from nearby extragalactic sources. We discuss both the energy regime of spatial diffusion and the quasirectilinear one leading to just angular diffusion at higher energies. We obtain analytic results for the anisotropies from a single source, which are validated using two different numerical simulations. For a scenario with a few sources in the local supercluster (with the closest source at a typical distance of few to tens of Mpc), we discuss the possible transition between the case in which the anisotropies are dominated by a few sources at energies below few EeV towards the regime in which many sources contribute at higher energies. The effect of a nonisotropic source distribution is also discussed, showing that it can significantly affect the observed dipole.